Biopharmaceutical And Microbiological Evaluation of Some Ceftriaxone-Sulbactam Products for Safety and Efficacy - Sunday Olajide Awofisayo (Journal of Medical Biomedical and Applied Sciences, 2021)
The concept of β-lactam antibiotics in combination with β-lactamase inhibitor to combat β-lactamase producing organism is a scientific norm for therapeutic success. This study seeks to compare some biopharmaceutical and microbiological parameters of selected ceftriaxone-sulbactam brands available in Nigeria with Rocephin®, as standard, with respect to efficacy and safety. Physical, physicochemical and microbiological tests for quality evaluation were performed alongside clinical / microbiological evaluations using typed and clinical isolates as indices for efficacy. The tested brands were adjudged satisfactory with respect to labeling and drug presentation. Two samples, SB-C and SB-D, revealed chemical contents lower than 90% for either ceftriaxone and/or sulbactam. However, all samples revealed satisfactory and similar microbiological safety and efficacy characteristics. Products SB-A, SB-B, SB-E, SB-F and SB-G demonstrated significantly higher antibacterial activity than the standard, (p<0.05). Samples SB-C and SB-D were not chemically equivalent to the other generic products of ceftriaxone-sulbactam evaluated. The presentation of ceftriaxone with β-lactamase inhibitor demonstrated similar biopharmaceutical properties but superior antimicrobial properties/ efficacy than the standard.